Zambia - The Relevance of a Rules-Based Maize Marketing Policy : An Experimental Case Study of Zambia - World Bank (Washington, DC, 2012)
A critical barrier to achieving food security and rural income growth in the mixed food marketing systems characterizing many Eastern and Southern African countries revolves around the way that governments and the private sector interact. In shortage years, governments may question the capacity of the private sector to import maize, and thus arrange imports on their own to cover the shortfall. At the same time, traders' import decisions depend on their expectations regarding governments' response to food shortages. Social dilemmas can arise if traders are uncertain about future government behavior or lack trust in official announcements. This paper argues that well-functioning markets depend on transparent and predictable government behavior underpinned by mutual trust and cooperation. The authors report on an economic policy experiment based on a stylized model of the Zambian maize market. The experiment facilitates a comparison between the current government policy of discretionary interventionism and a rules-based policy in which the government precommits itself to a future course of action. A simple precommitment rule can overcome the social dilemma by reducing the risk of food crises and provide appropriate incentives for private traders' participation in the market, thereby enhancing economic efficiency. Exploring mechanisms that can support more predictable and rules-based policy responses to food shortages may therefore be beneficial to the Government of Zambia and to other governments in the region.